Dampak Operasional Merger Perbankan: Sintesis Literatur dan Implikasinya terhadap Industri Perbankan - Rahmat Fajar Ramdani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
Mergers and acquisitions have served as a primary strategy for global banking consolidation over the past three decades, including in Indonesia, which is currently undergoing one of its most massive consolidation waves—one notable example being the emergence of Bank Syariah Indonesia. This article aims to provide a narrative review of the literature on the operational impacts of mergers on bank performance, with a particular focus on implications for the Indonesian context. Based on a systematic search of the Scopus database, 52 peer-reviewed articles published between 2000 and 2025 were analyzed using a narrative thematic synthesis approach. Five main themes were identified: cost efficiency, service quality, risk management, human resource and cultural integration, and information systems and technology integration. The key findings indicate that although 73.1% of studies report post-merger improvements in cost efficiency, these benefits are highly contingent upon the quality of post-merger integration especially in the areas of human resources, organizational culture, and information technology with IT integration failure rates reaching as high as 75%. Domestic mergers consistently achieve efficiency gains more rapidly than cross-border mergers, whereas risk implications depend heavily on the type of merger and the quality of integration. Policy implications include the need for the Financial Services Authority (Otoritas Jasa Keuangan) to monitor post-merger integration quality, provide integration guidelines for smaller banks, take into account the specific characteristics of Islamic banks, and ensure a streamlined, non-burdensome licensing process. Further research particularly empirical studies on banking mergers in Indonesia—is urgently needed to test the generalizability of global findings to the local context.